EFEKTIVITAS MODEL DISCOVERY LEARNING DAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN MATEMATIKA KELAS 4 SD GUGUS IMAM BONJOL - Dini Widyastuti; Suhandi Astuti (Jurnal Karya Pendidikan Matematika, 2020)
This research aims to knowed the Discovery Learning model is more effective than Problem Based Learning model seen from critical thinking skills of mathematic for students grade 4. This research is a Pre-Experimental Design with the design of Static Group Comparison.X variable of the research is Discovery Learning (X1), Problem Based Learning (X2), and critical thingking as (Y) variable. Subjects in this research is a 93 students grade 4 SD Gugus Imam Bonjol, Salatiga. The techique data collection used techique test is that description test and non description test is sheet of oservation and rubric critical thinking. Based on research T result test in experiment of group 1 and 2 experiment score symp. sig (2-tailed) of 0,037<0,05 and the conclusion that Ho is refused and Ha is accepted. Then could be conclued as application Discovery Learning model is better than Problem Based Learning model seen from critical thingking skills of mahematic grade 4 SD Gugus Imam Bonjol, Salatiga.